Edukacja medialna z perspektywy edukacyjnej analizy transakcyjnej - ŁĘSKI, ZBIGNIEW (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Zbigniew Łęski, Media education from the perspective of educational transactional analysis, Interdisciplinary Contexts of Special Pedagogy, No. 23, Poznań 2018. Pp. 103–115. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.23.06 Educational transactional analysis is one of the main branches of transactional analysis – a concept, which was developed with psychotherapy in mind. Its tools and clear terminology allow for both theoretical and empirical analysis of many aspectspertaining to the specificity of human functioning in the world of new media. The article shows the possibilities of its application and presents a review of previous theoretical and empirical initiatives that deal with this issue.